Basic Marketing / A Global-Managerial Approach International Student Edition - Mccarthy Jerome E; Perreault William D (Irwin Mcgraw-Hill, 1993)
Marketing Role in Society, Marketing's Role within the Firm, Economics Fundamentals, Evaluating Opportunities in Uncontrollable Environments, Demographic Dimensions of the U.S. Consumer Market, Elements of Product Planning, Place and Development of Channel Systems, Retailing, Wholesaling, Physical Distribution, Personal Selling, Mass Selling, Marketing Arithmetic, Planning and Implementing Marketing Programs, Marketing Strategy Planning for International Markets, Career Planning in Marketing, Cases.
Marketing Role in Society, Marketing's Role within the Firm, Economics Fundamentals, Evaluating Opportunities in Uncontrollable Environments, Demographic Dimensions of the U.S. Consumer Market, Elements of Product Planning, Place and Development of Channel Systems, Retailing, Wholesaling, Physical Distribution, Personal Selling, Mass Selling, Marketing Arithmetic, Planning and Implementing Marketing Programs, Marketing Strategy Planning for International Markets, Career Planning in Marketing, Cases.